Preparing foundation-year students for medical studies in a problem-based learning environment: Students׳ perceptions - Xiangyun, Du (2016)
PurposeTo contribute to the field of preparing new students for their medical studies and to investigate how foundation-year medical students perceive the progression of appropriate learning skills for studying in a PBL medical curriculum via the support of a course aiming at facilitating students with these skills. MethodsA 10-point scale online questionnaire consisting of 20 questions was used for data collection. 50 out of the 59 (19 males and 31 females) students responded and self-evaluated a list of learning skills according to the course objectives before and after the course. Cronbach׳s alpha was used to test for internal consistency and reliability of the collected data and Principal Component Exploratory Factor Analysis was performed. Paired t-test was used to examine differences between pre- and post-analysis data. ResultsThe internal consistency of the questionnaire was sufficient. Factor analysis identified four factors: 1) Ability to search for, share, and present information, 2) Ability to develop learning tools and express opinions, 3) Ability to use diverse learning sources, and 4) Ability to participate in discussion and reflect. Overall improvement between pre- and post-test was high (2.38). Paired t-tests showed significant improvements (p<.001) for each of the 4 factors. The four factors together explained 60.7% percent of variance in the data. DiscussionStudents reported large improvements among learning skills required in a problem-based medical curriculum, and suggests that students in a premedical foundation year can benefit from a course aiming at preparing students for their future learning in a PBL environment. A shortcoming was considered the retrospective nature of the pretest, possibly biasing the results of the comparisons.